2017
DOI: 10.1515/jpm-2016-0225
|View full text |Cite
|
Sign up to set email alerts
|

Clinical chorioamnionitis at term VII: the amniotic fluid cellular immune response

Abstract: Objective 1) To characterize the cellular composition of the amniotic fluid of patients diagnosed with clinical chorioamnionitis at term, as a function of the presence or absence of microorganisms determined by cultivation techniques, and 2) to characterize the cytokine production by white blood cells present in the amniotic fluid using flow cytometry-based techniques. Material and Methods Amniotic fluid samples from 20 women with the diagnosis of clinical chorioamnionitis at term were analyzed using cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
87
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 147 publications
9
87
0
Order By: Relevance
“…Regardless of their origin, amniotic fluid neutrophils are a part of the innate immune host defense mechanisms that take place in the amniotic cavity of women with intra-amniotic infection 77, 163, 164 . This concept is supported by evidence demonstrating that amniotic fluid neutrophils 1) are a source of anti-microbial products 90, 165168 and cytokines 69 , 2) can trap and kill bacteria invading the amniotic cavity by forming neutrophil extracellular traps (NETs) 68 , and 3) can phagocytize microorganisms commonly found in the lower genital tract, e.g., Streptococcus agalactiae (also known as Group B Streptococcus or GBS), Ureaplasma urealyticum , Gardnerella vaginalis , and Escherichia coli 132 . Together, these findings show that even in the absence of microbial invasion, neutrophils are present in the amniotic fluid throughout gestation and ready to participate in the host defense mechanisms taking place in the amniotic cavity.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Regardless of their origin, amniotic fluid neutrophils are a part of the innate immune host defense mechanisms that take place in the amniotic cavity of women with intra-amniotic infection 77, 163, 164 . This concept is supported by evidence demonstrating that amniotic fluid neutrophils 1) are a source of anti-microbial products 90, 165168 and cytokines 69 , 2) can trap and kill bacteria invading the amniotic cavity by forming neutrophil extracellular traps (NETs) 68 , and 3) can phagocytize microorganisms commonly found in the lower genital tract, e.g., Streptococcus agalactiae (also known as Group B Streptococcus or GBS), Ureaplasma urealyticum , Gardnerella vaginalis , and Escherichia coli 132 . Together, these findings show that even in the absence of microbial invasion, neutrophils are present in the amniotic fluid throughout gestation and ready to participate in the host defense mechanisms taking place in the amniotic cavity.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have shown that intra-amniotic infection is characterized by the infiltration of neutrophils and monocytes/macrophages 23, 27, 6769, 129132 . It was recently suggested that amniotic fluid ILCs were also implicated in regulating intra-amniotic infection and inflammation in preterm gestations 119 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical chorioamnionitis is the most frequent pregnancy-related infection diagnosed in labor and delivery units worldwide [1]. The prevalence of this condition in term gestations ranges from 5% to 12% [2], while in preterm gestations, it is diagnosed in 20% of patients with preterm premature rupture of the membranes (PROM) [35] and in about 10% of patients with preterm labor and intact membranes [611].…”
Section: Introductionmentioning
confidence: 99%